UNSTABLE ANGINA TREATMENT IN VARIOUS PERIODS OF GEOMAGNETIC ACTIVITY - Parshina, S. S.; Tokayeva, L. K.; Afanas’yeva, T. N.; Samsonov, S. N.; Petrova, V. D.; Dolgova, E. M.; Manykina, V. I.; Vodolagina, E. S. (Одеські астрономічні публікації, 2014)
In 145 patients with unstable angina (UA) there was analized an efficiency of a drug therapy at different types of heliogeophysical activity (HA) during the 23th solar cycle. 83 patients were examined at the period of a lower HA (Kp-index 16,19±0,18), and 62 patients – at the period of a higher HA (Kp-index 17,25±0,21, p<0,05). Baseline severity of patients’condition with UA at the moment of hospitalization at the studied periods did not differ, but the effectiveness of the therapy depended on the period of HA. At the period of a higher HA antianginal effect was stronger than at the lower period of HA (2,27±0,16 points and 1,75±0,12 points, p<0,05), and the need in nitroglycerin on the background of a drug therapy disappeared for 5-7 days quicker than at the period of a lower HA. Maximal hypotensive effect at a higher HA was achieved quicker – on the 3rd day of the treatment, and at a lower HA – only up to hospital discharge (p<0,05). Blood viscosity did not normalize in both of the studied periods, but in small vessels there was noted a decrease of a BV (p<0,05). So, at a higher HA the effectiveness of a drug therapy in patients with UA is higher than at the period of a lower HA.